Pengaruh Pembayaran Digital (Qris) Dan Inovasi Produk Terhadap Peningkatan Pendapatan UMKM Kuliner Di Jalan Pangkalan Asem Raya Jakarta - Sigit Prasetyo; Anita Maulina (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. This research examined the crucial role of digital payments, particularly through QRIS, and product innovation in increasing the revenue of culinary Micro, Small and Medium Enterprises (MSMEs) on Jalan Pangkalan Asem Raya, Jakarta. MSMEs contributed significantly to the Indonesian economy but still faced challenges in adopting digital technology and implementing innovation effectively. This research aimed to analyze how much impact digital payment and product innovation, both partially and simultaneously, had on increasing MSME income. Using a quantitative approach, this research involved the variables of digital payment (X1), product innovation (X2), and increased MSMEs income (Y). Data were collected and analyzed using methods such as analysis of the average respondents’ responses, data quality tests (validity and reliability), hypothesis testing, correlation and determination coefficient analysis, and partial (T-test) and simultaneous (F-test) significance tests. The results showed that digital payments and product innovation significantly influenced the increase in MSMEs’ income. Digital payments, particularly QRIS, were proven to ease transactions and expand market reach, creating a foundation for efficient operations. MSMEs also showed high adaptive capabilities in innovating, especially in responding to market tastes. Simultaneously, these two variables had a strong influence, where 74.7% of the variation in MSMEs’ income increase could be explained by digital payments and product innovation, while the remaining 25.3% was influenced by other factors outside the model. Nonetheless, challenges related to budget allocation and time for research and innovation development still need to be improved for long-term sustainability. In conclusion, the synergy between advances in payment technology and the spirit of product innovation was key to the growth strategy of MSMEs in urban areas such as on Jalan Pangkalan Asem Raya Jakarta. This research recommended the optimization of digital transaction recording, special budget allocation for product innovation, and improved income target planning strategies to promote sustainable growth. Keywords: Digital Payment (QRIS), Product Innovation, Revenue Increase, MSME, Jakarta.